2002
DOI: 10.1002/0471140864.ps0406s27
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Storage of Proteins

Abstract: This unit provides a summary of some of the issues that researchers face when attempting to store purified proteins. It briefly explains the stresses that induce protein aggregation the major causes for chemical degradation. It also discusses how to use various storage strategies to increase the long-term stability of proteins. When appropriate it points out critical mistakes to avoid. This unit provides a summary of some of the issues that researchers face when attempting to store purified proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Indeed, some molecules appeared to have adopted a more compact structure (migrating slightly faster than the native α 2 M band), while others had formed smaller species (based on the relative mobility of these species they are likely to be dimers, lower band in lane 3) and still others had formed higher molecular weight species (due to non-covalent self-association of the protein). As a commonly used strategy for long-term storage of proteins involves freezing [ 51 ], the protein was analyzed after storage in PBS/Az at -20°C for 10 days; less than 50% of the purified α 2 M was found to migrate to a position corresponding to native α 2 M when assessed by native PAGE, the remainder of the protein migrated to a position corresponding to transformed α 2 M ( Fig 1B ). The extent of α 2 M transformation was found to be reduced, but not abolished, by rapid freezing of the protein in liquid nitrogen (-196°C) prior to storage at -20°C ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some molecules appeared to have adopted a more compact structure (migrating slightly faster than the native α 2 M band), while others had formed smaller species (based on the relative mobility of these species they are likely to be dimers, lower band in lane 3) and still others had formed higher molecular weight species (due to non-covalent self-association of the protein). As a commonly used strategy for long-term storage of proteins involves freezing [ 51 ], the protein was analyzed after storage in PBS/Az at -20°C for 10 days; less than 50% of the purified α 2 M was found to migrate to a position corresponding to native α 2 M when assessed by native PAGE, the remainder of the protein migrated to a position corresponding to transformed α 2 M ( Fig 1B ). The extent of α 2 M transformation was found to be reduced, but not abolished, by rapid freezing of the protein in liquid nitrogen (-196°C) prior to storage at -20°C ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…FFP is a complex biological material which contains a plethora of bioactive molecules (18). Although optimal conditions for storage are distinctive for each protein, it is well known that proteins generally alter structural integrity and activity as a result of refrigeration due to proteolysis, aggregation, and suboptimal buffer conditions (19). We have recently shown that refrigeration of FFP decreased its coagulation factors and diminished its beneficial effects on endothelial function and resuscitation in an animal model of HS (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although optimal conditions for storage are distinctive to each protein, it is well known that proteins generally lose structural integrity and activity as a result of storage at 4°C because of proteolysis, aggregation, and suboptimal buffer conditions. 24 Consequently, to prevent rapid degradation of proteins, preserve function, and prevent variable results, standard techniques in the basic science laboratories mandates –80°C storage of proteins used in experiments.…”
mentioning
confidence: 99%